Optimalisasi Sistem Informasi Manajemen dalam Penguatan Tata Kelola Lembaga Pendidikan Islam di Era Revolusi Industri 4.0 dan Society 5.0 - Hendra Kurniawan; Ira Damayanti Hasibuan; Sallima Nur Alaina Rambe; Maulana Hakim; Rafli Pasha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The era of the Industrial Revolution 4.0 and Society 5.0 brings significant changes in various aspects of life, including education. Islamic educational institutions, as vital entities in shaping the character and knowledge of younger generations, are required to undergo digital transformation to improve governance and management quality. Management Information Systems (MIS) serve as a primary tool that can integrate administrative processes, data management, and decision-making effectively, efficiently, and accountably. This study discusses the optimization of MIS in strengthening the governance of Islamic educational institutions, focusing on the challenges and opportunities faced in this era of advanced technology. The research method employed is qualitative descriptive, reviewing literature and previous studies concerning MIS and the management of Islamic educational institutions amidst digital technological dynamics. The findings indicate that optimizing MIS demands developing human resource capacities, improving technological infrastructure, and fostering an organizational culture adaptive to digital change. Although challenges such as infrastructure limitations, cultural resistance, and data security issues exist, opportunities arising from technologies like cloud computing and big data pave the way for more modern and competitive institutional management. Strengthening governance through MIS not only enhances efficiency but also supports accountability and transparency in line with Islamic values that emphasize honesty and responsibility. Thus, optimizing MIS is a key strategy to ensure Islamic educational institutions can adapt and thrive in the Industrial Revolution 4.0 and Society 5.0 era.